PLC Human Machine-Interfaces Based System for Vietnam Drip Coffee Maker Application - Nur Alif Mardiyah; Akhmad Hakam Sudrajat; Amrul Faruq (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2018)
The most recent development of digital technology is rapidly growing having a strong impact in daily activities. Automation is a trend in society to make those activities become easier. Moreover, efficiency has played the main role in the automation concept. For example, when making a drink which requires to accurately mix all required ingredients, like sugar, tea, and also coffee, the process may take time. Meanwhile, other more important processes have waited to be carried out. The idea of fasten up these activities may be preferable, exemplified by making an automatic drink maker machine. Moreover, coffee has been popular drink fancied by most people on the society. Hence, due to the high load of the people’s activity, everything is required to be instant and efficient. According to this trend, to provide an efficient, easy, and good management, we need to create an automatic, fast, and accurate system control which can be implemented by using Programmable Logic Controller (PLC) and Human-Machine Interface (HMI). Meanwhile, in this research, Omron PLC and HMI are utilized to build an automatic drink maker device of Vietnamese Drip Coffee designed to resolve the society’s needs of coffee with higher efficiency of serving process. The automatic coffee maker device of Vietnamese Drip Coffee based on PLC and HMI is a device designed to simplify the making process of Vietnamese Drip Coffee in hot condition. This device can be operated by only touching/tapping on its coffee menu choices. The design of this device has the main purpose to operate and test the control system based on PLC and HMI to control and monitoring the automatic process of producing Vietnamese Drip Coffee started from choosing the coffee types until mixing process.